Analysis of quality assurance in the hospital sector of the People’s Republic of China - Barbara Darimont; Louis W Margraf (Journal of Global Health Reports)
Quality assurance of medical treatment in hospitals has become increasingly important in the People\'s Republic of China in recent years. Health sector reforms have mainly focused on cost reduction, leading to undesirable developments in the quality of medical treatment. One serious problem concerns aggression towards medical personnel in cases where treatment has proven unsuccessful. This article reviews the general situation of hospitals, the payment of doctors, the legal situation, and finally the organisation of medical quality management in the People\'s Republic of China. The study is based on a literature research in English and Chinese, which in particular includes recent literature from 2015 onwards. In addition, laws, draft laws and legal research are systematically processed. As such, the People\'s Republic of China has already established a system of DRGs and quality management for hospitals, but it faces many practical problems. Especially data quality has to be improved. Organisationally, further control functions have to be implemented and regular supervision is missing. Experiments with pay-for-performance systems have shown that this seems to be a way to improve medical treatment. Ultimately, the reform of the pay structure for hospital doctors must be addressed first, before further measures in terms of quality assurance can be pursued effectively. This might be the main topic for further research to be done.